2016
DOI: 10.1155/2016/5389181
|View full text |Cite
|
Sign up to set email alerts
|

miR‐21 Reduces Hydrogen Peroxide‐Induced Apoptosis in c‐kit+ Cardiac Stem Cells In Vitro through PTEN/PI3K/Akt Signaling

Abstract: The low survival rate of cardiac stem cells (CSCs) in the infarcted myocardium hampers cell therapy for ischemic cardiomyopathy. MicroRNA-21 (miR-21) and one of its target proteins, PTEN, contribute to the survival and proliferation of many cell types, but their prosurvival effects in c-kit+ CSC remain unclear. Thus, we hypothesized that miR-21 reduces hydrogen peroxide- (H2O2-) induced apoptosis in c-kit+ CSC and estimated the contribution of PTEN/PI3K/Akt signaling to this oxidative circumstance. miR-21 mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 73 publications
1
26
0
Order By: Relevance
“…Thus, it appears that miR-21 plays an active role in disrupting the PTEN-AKT-mTOR pathway. Similar result was also observed in cardiac stem cells, where miR-21 reduced hydrogen peroxide- (H 2 O 2 -) induced apoptosis, as evidenced by the downregulation of caspase-3 and Bax and upregulation of the antiapoptotic Bcl-2 [ 205 ]. Overexpression of miR-21 suppressed the expression of PTEN, a direct target of miR-21, with simultaneous increased in the phosphorylation state of AKT.…”
Section: Mtor In Cardiovascular Diseasessupporting
confidence: 68%
“…Thus, it appears that miR-21 plays an active role in disrupting the PTEN-AKT-mTOR pathway. Similar result was also observed in cardiac stem cells, where miR-21 reduced hydrogen peroxide- (H 2 O 2 -) induced apoptosis, as evidenced by the downregulation of caspase-3 and Bax and upregulation of the antiapoptotic Bcl-2 [ 205 ]. Overexpression of miR-21 suppressed the expression of PTEN, a direct target of miR-21, with simultaneous increased in the phosphorylation state of AKT.…”
Section: Mtor In Cardiovascular Diseasessupporting
confidence: 68%
“…Accordingly, these data identified PTEN as an endogenous defender against inflammation-mediated cellular damage in nasal epithelial cells. Previous studies have also illustrated the beneficial role of PTEN in acute kidney injury (28), diabetes (71), cardiomyopathy (72) and chronic fatty liver disease (73). Therefore, an approach to reverse PTEN activity could be considered as adjuvant therapy to enhance anti-inflammatory treatments in patients with chronic nasal and sinus inflammation, but this needs to be investigated further.…”
Section: Discussionmentioning
confidence: 97%
“…The results of the present study demonstrate that lncRNA5322 or miR-21 transfection lead to upregulation of the PI3K/AKT signaling pathway in HFTs. Deng et al (32) suggested that miR-21 reduced hydrogen peroxide-induced apoptosis in c-kit+ cardiac stem cells in vitro via PTEN/PI3K/AKT signaling. The findings of the present study indicate that agomir-21 blocks lncRNA5322-induced upregulation of the PI3K/AKT signaling pathway during HFT differentiation.…”
Section: Discussionmentioning
confidence: 99%